PENGARUH KEGIATAN 3M (MELIPAT, MENGGUNTING, MENEMPEL) TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TK IMMANUEL KIDS MEDAN AMPLAS - Angel Purba, Folin; Elya Siska Anggraini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study .aims to determine the effect of 3M activities (folding, cutting, sticking) on the fine motor skills of 5-6 year old children at Immanuel Kids Kingdergarten, Medan Amplas. This study used a quantitative apporoach with a structured experimental method using a One Group Pretest- Posttest Design, involving a sample of 22 children. Data collection was conducted using a normality test and a t-test to test hypotheses. The children’s scores increased from 10,23 (total score 225) in the pretest to 12,41 (total score 273) in the posttest. Because the calculated t-value was greater then the table t-value, the alternative hypothesis was accepted. Based on these findings, it can be concluded that the 3M activities (folding, cutting, and sticking) have a significant positive effect on improving the fine motor skills of 5-6 year old children at Immanuel Kids Kingdergarten, Medan Amplas.